Control of Biological Exposure to UV Radiation in the Arctic Ocean: Comparison of the Roles of Ozone and Riverine Dissolved Organic Matter - Gibson, JAE; Vincent, WF; Nieke, B; Pienitz, R (2000)
Reports of severe stratospheric ozone depletion over the Arctic have heightened concern about the potential impact of rising ultraviolet-B (UV-B) radiation on north polar aquatic ecosystems. Our optical measurements and modelling results indicate that the ozone-related UV-B influence on food web processes in the Arctic Ocean is likely to be small relative to the effects caused by variation in the concentrations of natural UV-absorbing compounds, known as chromophoric dissolved organic matter(CDOM), that enter the Arctic basin via its large river inflows. The aim of our present study was to develop and apply a simple bio-optical index that takes into account the combined effects of attenuation by atmospheric ozone and water column CDOM, and photobiological weighting for high-latitude environments such as the Arctic Ocean. To this end, we computed values for a biologically effective UV dose rate parameter ('weighted transparency' or T*) based on underwater UV measurements in highlatitude lakes and rivers that discharge into the Arctic Ocean; measured incident UV radiation at Barrow, Alaska; and published biological weighting curves for UV-induced DNA damage and UV photoinhibition of photosynthesis. The results underscore how strongly the Arctic Ocean is influenced by riverine inputs: shifts in CDOM loading (e.g., through climate change, land-use practices, or changes in ocean circulation) can cause variations in biological UV exposure of much greater magnitude than ozone related effects.